Fragile X-Associated Neuropsychiatric Disorders (FXAND) - Hagerman, Randi J.; Protic, Dragana; Rajaratnam, Akash; Salcedo-Arellano, Maria J.; Aydin, Elber Yuksel; Schneider, Andrea (Frontiers in Psychiatry, 2018)
Neuropsychiatric disorders are the most common problems associated with the premutation, and they affect approximately 50% of individuals with 55 to 200 CGG repeats in the FMR1 gene. Neuropsychiatric disorders in children with the premutation include anxiety, ADHD, social deficits, or autism spectrum disorders (ASD). In adults with the premutation, anxiety and depression are the most common problems, although obsessive compulsive disorder, ADHD, and substance abuse are also common. These problems are often exacerbated by chronic fatigue, chronic pain, fibromyalgia, autoimmune disorders and sleep problems, which are also associated with the premutation. Here we review the clinical studies, neuropathology and molecular underpinnings of RNA toxicity associated with the premutation. We also propose the name Fragile X-associated Neuropsychiatric Disorders (FXAND) in an effort to promote research and the use of fragile X DNA testing to enhance recognition and treatment for these disorders.